Low serum free IL-18 is a novel potential marker for predicting infectious events in patients at dialysis initiation - Tawara-Iida, Takashi; Usui, Joichi; Ebihara, Itaru; Ishizu, Takashi; Kobayashi, Masaki; Maeda, Yoshitaka; Kobayashi, Hiroaki; Yamagata, Kunihiro; Nakamura, Hideko; Takada, Kenji; Kozaki, Koichi; Iwabuchi, Satoshi; et al. (Clinical kidney journal, 2025)
Compared to the general population, individuals who are undergoing hemodialysis are at a higher risk of contracting severe infectious diseases, and their mortality rate from infectious diseases is also higher. We investigated the serum free interleukin-18 [free state of interleukin-18 (IL-18)] concentration as a prognostic factor for hemodialysis patients' infection risk. The Ibaraki Dialysis Initiation Cohort (iDIC) study is a multicenter prospective cohort investigation of patients undergoing a new initiation of dialysis in a local region of Japan. We performed a survival analysis of several events requiring hospitalization and compared the Kaplan-Meier curves of the "low" and "high" serum free IL-18 concentration groups. To adjust for confounding factors, we also performed a Cox proportional hazards analysis. We analyzed the serum free IL-18 concentration of samples from 295 patients randomly selected from the blood sample bank of the iDIC study. The mean free IL-18 concentration was 8.7 ± 5.3 pmol/l. The cumulative incidence of infectious events was significantly higher in the low free IL-18 group (<6.0 pmol/l, log-rank test < .01). The Cox proportional hazards analysis revealed that low serum free IL-18 (<6.0 pmol/l) was an independent factor associated with the development of infectious events. Total IL-18 and IL-18BP (binding protein) showed no association with infectious events. A low serum free IL-18 concentration in the dialysis initiation period is a potential marker for predicting the development of severe infection in these patients.